Pengembangan Multimedia Pembelajaran Berbasis Adobe Flash Pada Kompetensi Dasar Menganalisis Jenis-jenis NAPZA di SMK Pekerjaan Sosial - Rosyid, Feby Khoerur Rijal; Rohaeni, Neni; Rinekasari, Nenden Rani (FamilyEdu: Jurnal Pendidikan Kesejahteraan Keluarga, 2020)
This research departs from the problem, namely the material types of drugs that are abstract and a little difficult to explain which needs explanation equipped with pictures or videos because they cannot choose the types of drugs directly in the class and the unavailability of source books from the subjects students stick to the material presented by the teacher in the classroom. The teacher has used learning media in delivering material but it is limited to projection text in the form of power points that contain and images that make learning tend to be oblique and monotonous. This study aims to develop multimedia learning based on Adobe Flash on the basic competencies of analyzing the types of drugs in the Social Work Vocational School. The method used in this research is Research and Development (RD) with the Planning, Production, and Evaluation (PPE) model developed by Richey and Klein. Data techniques in research using two of the latest research instruments, documentation and expert assessment validation format. The expert assessment was carried out by four PKK FPTK UPI lecturers consisting of two drug material experts and two instructional media experts. The results of the validation carried out by two drug material experts and two instructional media experts were stated "very feasible" to be used with revisions according to the suggestions and comments of the validator so that they could be used as teaching materials.